ChemInform Abstract: Regioselective Synthesis of Polycyclic Aza‐Oxa and Aza‐Oxa‐Thia Heteroarenes as Colo‐205 and HepG2 Carcinoma Cells Growth Inhibitors. Issue 48 (2nd December 2014) - Ram, Vishnu Ji; et al., et al.
Abstract An elegant regioselective synthesis of fused tetra‐ and pentacyclic heteroarenes based on ring transformation reactions of appropriate lactones with hydrazine is given.